PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI, TEKNOLOGI INFORMASI, DAN KOMUNIKASI TERHADAP KESIAPAN PEMERINTAH DALAM MENERAPKAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi empiris pada Pemerintah Kabupaten Indragiri Hilir) - Iznillah, Muhammad Luthfi; Azlina, Nur; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The enactment of government regulation number 71 year 2010 about government accounting standards based accrual and also enactment permendagri 64 2013 about the application of government accounting standards based accrual on regional government bring big changes in financial reporting system in indonesia , namely change from the base cash toward accrual become the bases full in accrual recognition government financial transactions .This research aims to analyse the influence of variable quality of human resources, the commitment of the organization , information technology , and communication against readiness of local governments in applying the government accounting standards based accrual. This research conducted in Indragiri Hilir district using data primer namely data from questionnaires filled by respondents.Object used in this research is a work unit ( skpd ) particularly office, the agency and the department under the district government Indragiri Hilir.The population in this research was all of the employee of financial management agency on the office and environment agency in the district government Indragiri Hilir.Of respondents selected with the methods of sampling purposive, data analysis in this research using methods regression analysis program double with a version of windows spss 17.0 The result of the research indicated that the variable the quality of human resources and commitment of its effect on organization readiness in applying the government accounting standards based accrual .While variable information technology and variable communication did not influenceKeywords: government accounting standards ,accrual based, readiness of the government , the quality of human resources , the commitment of the organization , information technology , and communication